Impact of Covid-19 Virus on Ophthalmology Residents and Fellows in a Tertiary Care Hospital: Doi: 10.36351/pjo.v37i4.1189 - Nawaz, Maryum (Pakistan Journal of Ophthalmology, 2021)
Purpose: To determine the impact of COVID-19 pandemic on the training of Ophthalmology residents and fellows in a tertiary care hospital. Study Design: Cross sectional survey. Place and Duration of Study: The study was conducted in a tertiary care hospital, Peshawar from august 1st to august 20th 2020. Methods: A self-designed questionnaire was distributed among 50 ophthalmology residents and fellows. Under-graduate students, house officers and post-graduate trainees from other specialties were excluded. Questions comprised of demographic data, and questions which were meant to investigate the changes experienced by the trainees during COVID-19. The data was analyzed by SPSS Software (Version 19). Results: Among 50 participants of this study, 16 (32%) were females and 34 (68%) were males. The age ranged from 27 to 35 years. There was no statistically significant difference in the perspectives of resident trainees and fellows regarding negative impact of COVID-19 on their training. Ninety-five percent of the residents and fifty five percent of the fellows had effect on their clinical skills with p values of less than 0.05. Hundred percent residents agreed that online case presentation could not replace the traditional long rounds and simulator based training could improve the surgical skills in pandemic. Twenty five (60.97%) trainees and 6 (66.66%) fellows mentioned that pandemic affected them psychologically and they felt fear while working. Conclusion: COVID-19 has adversely affected the training of post graduate trainees. Training directors should ensure to provide modern technological tools to improve trainees’ clinical and surgical skills until the crisis is over. Key Words: COVID-19, Ophthalmology, Training, Conference.